PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PROBLEM POSING UNTUK MELATIH KREATIVITAS DALAM PEMECAHAN MASALAH - Wahyuni, Nur; Lukito, Agung; Mariana, Neni (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
Creativity is very important in today's modern era so it must be increased by making efforts such as creating learning tools to train students' creativity to raise their problems while solving those problems. The purpose of this study is (1) to describe the quality of learning by using the problem-posing approach to train students' creativity in problem solving; (2) to describe the creativity of students in solving problems in the perimetri and area of rectangle based on problem-posing. This research is a development research. Data collection techniques using questionnaires, tests, observations, and validation methods. The results showed that (1) The problem-posing approach has the quality to increase the creativity of students in solving problems of perimetri and area of rectangle; (2) After learning with problem posing showed that the students' creativity test results increased from the previous test.